Anatomical Insights Into Dry Lumbar Vertebrae In The Pakistani Population: Applications In Modern Spinal Surgery - Hina, Mohtasham; Rasheed, Ammara; Atta, Irum; Tasleem, Maria; Qureshi, Tayyaba; Tafweez, Raafea (Journal of Rawalpindi Medical College, 2025)
Objectives: The lumbar spine plays a crucial role in weight bearing in human beings. This study focused on determination of different parameters in local Pakistani population to enhance the clinical diagnosis and spinal surgeries. Methods: This cross-sectional observational study was done in the Anatomy Museum of King Edward Medical University during the year 2024 on a collection of 200 dry lumbar vertebrae. All the vertebrae with intact bony features were included in this study, while damaged or vertebrae with gross abnormality were excluded. All parameters were taken with the help of a Vernier calliper and expressed in millimetres. Vertebral body parameters recorded include anteroposterior length of upper and lower border on both right and left sides, and transverse length of body at superior border, at middle of body and inferior border was recorded. Height or vertebral body in midline anteriorly, along with anteroposterior and transverse dimensions of vertebral canal, was also recorded. Results: Mean and standard deviation of all parameters were calculated, and a paired t-test was applied on paired dimensions, e.g anteroposterior diameters of the upper and lower borders of both right and left sides. That does not reveal any statistically significant difference. Significant difference was found in the transverse length of the vertebral body at the upper and lower borders with the middle of the vertebral body (p<0.01) Conclusion: These findings will help precise diagnosis of various clinical conditions arising due to changes in morphology and in designing prostheses for surgical implications. Key words: Lumbar vertebra, spinal canal, body of vertebra